Investigating the Treatment of Gastric Cancer by Accelerated Particle Energy in Nuclear Accelerators - Azizi, Noor Mohammad; Mohammadi, Zaman (Journal of Natural Sciences – Kabul University, 2024)
A particle accelerator is a means to increase the kinetic energy of charged particles such as electrons, protons, alpha particles, and other heavy ions. The research method of this article is a comparative review, and it has been tried to investigate the treatment of gastric cancer by the energy of accelerated particles in nuclear accelerators. First, nuclear accelerators are introduced, followed by the rays used in the treatment of gastric cancer, the energies used in the treatment of gastric cancer, the accelerators used in the treatment of gastric cancer, and energy comparison. Accelerated particles have been investigated in the treatment of gastric cancer. The goals and importance of this research show that the best accelerator for gastric cancer treatment is Link, the best TOMO method, and the energy range (6-25) MeV. Because using the TOMO method has fewer side effects, the treatment is done quickly, effectively, and more compatible with the cells around the cancerous tumor.